Analisis Pembelajaran Daring Berbasis WhatsApp pada Tema 4 Kelas VI SD Negeri Pengkol Jepara - Imam Wahyudi; Ikha Listyarini; Ferina Agustini (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to describe the implementation and problems of WhatsApp-based online learning on theme 4 grade VI SD Negeri Pengkol Jepara. This research method is a qualitative research using data collection techniques in the form of observation, interviews, questionnaires and documentation. Based on the findings of the research, it can be concluded that the implementation of WhatsApp-based online learning at SD Negeri Pengkol Jepara has been carried out well. The school's online learning implementation uses WhatsApp as the main media or platform in carrying out online learning. There are several problems experienced by teachers including the difficulty of ownership of student facilities which are very limited and then the learning time given by the teacher is not as expected by the teacher. As for the problems experienced by students in online learning, among others, students do not really understand or even understand the material that has been delivered by the teacher because it is only a learning video. Then the students were too bored and lacked interest in listening and understanding the learning video until it was finished. Lack of understanding of students in the end in doing assignments or tests cannot be maximized, carelessly not even doing assignments.